2014
DOI: 10.1111/cge.12384
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent for human genetic and genomic studies: a systematic review

Abstract: As genetic and genomic studies grow in scale, there are ethical concerns related to the collection and use of genetic information. The emergence of large public databases potentially redefine the terms of participation in genetic and genomic research, and suggests the changing application of traditional ethical principles such as privacy or consent. For this study, we wanted to see whether such developments are reflected in the informed consent processes in human genetic and genomic studies. Therefore, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…The discrimination between men and women may result in the latter feeling less comfortable sharing their private information with their spouses. Parallel with our results, in the literature, younger age has been associated with greater privacy concerns (Khan A et al, 2014). Oliver et al (Oliver et al, 2012) provided a very interesting interpretation for the difference between the age groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The discrimination between men and women may result in the latter feeling less comfortable sharing their private information with their spouses. Parallel with our results, in the literature, younger age has been associated with greater privacy concerns (Khan A et al, 2014). Oliver et al (Oliver et al, 2012) provided a very interesting interpretation for the difference between the age groups.…”
Section: Discussionsupporting
confidence: 89%
“…One reason for this may be the privacy concerns of women about genetic tests. However, the results of similar studies on gender differences are not consistent (Khan A, Capps BJ, Sum MY, Kuswanto CN, & Sim K, 2014). For example, Mezuk, Eaton, and Zandi (Mezuk, Eaton, & Zandi, 2008) found no association between genders about consent to donate a biological sample or allow genetic testing or storage of that sample while Green et al (Green et al, 2006) reported that it was men that mostly denied private companies access to their DNA.…”
Section: Discussionmentioning
confidence: 91%
“…Second, the innovativeness, and growth, of more detailed genetic analysis raises questions about the increasing chances of finding genetic predictions or diagnoses that are not related to the reason for the test (so-called incidental findings, or IFs): for example, risks for hereditary cancers amenable to risk-reducing interventions. Specifically, questions arise about how these might be anticipated and incorporated into the consent process and even whether they should be reported if not specifically sought [39]. Third, the familial nature of (some) genetic information raises issues about whether confidentiality can best be viewed at the individual or familial level and whose responsibility (if anyone’s) it is to communicate risk to at-risk relatives [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing amounts of empirical research being conducted on seeking consent to research, to date there is still relatively little literature available on seeking consent in low and middle income countries, specifically in relation to genetic and genomic research [10, 12-18]. Issues about how much information about genomic studies should be provided, and how best to do so, are under-researched [19]. This is an important gap in the literature given the increasing interest in genomic research in low-income settings and in particular in Africa, with initiatives such as H3Africa (www.H3Africa.org).…”
Section: Introductionmentioning
confidence: 99%